Genetic basis of thermal plasticity variation in Drosophila melanogaster body size - Lafuente, Elvira (2018)
This deposit is composed by the main article. The supplementary materials can be found on-line through the following link: https://journals.plos.org/plosgenetics/article?id=10.1371/journal.pgen.1007686#sec017